Enhancing Student Employability in Collaboration with the Industry: Case Study of a Partnership with Amazon Web Services Academy - Gokop L. Goteng; M. Mahruf C. Shohel; Faisal Tariq (MDPI AG, 2022)
The continuous increase in tuition fees in high education in many countries requires justification by the university authorities of what students receive from them in return. One of the key factors of student recruitment is values for money and quality learning experiences including hands-on industry training that can guarantee immediate employment for the graduates. This article describes redesigning the curriculum of a cloud computing undergraduate module in collaboration with Amazon Web Services (AWS) Academy. Industry-based practical hands-on labs were incorporated into this module for engineering students to improve their practical knowledge and skills related to the Internet of Things. Through an innovative approach, this practitioner research introduces industry best practices and hands-on labs in cloud computing. In this approach, academic theories were incorporated in cloud computing with their applications through industry attachment. It enables students to have both the theoretical and practical knowledge and skills for ensuring their careers in the field of cloud computing. The study finds that students tend to be more engaged and learn better when theoretical knowledge and understanding are combined with real-world applications through the attachment with the industry.